1999
DOI: 10.1086/314614
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and Chronic Hepatitis B Virus Infection in Africans and Variation in the Vitamin D Receptor Gene

Abstract: The active metabolite of vitamin D, 1,25 dihydroxyvitamin D3, is an important immunoregulatory hormone [1]. Its effects are exerted by interaction with the vitamin D receptor, which is present on human monocytes and activated T and B lymphocytes. Variation in the vitamin D receptor gene was typed in 2015 subjects from large case-control studies of three major infectious diseases: tuberculosis, malaria, and hepatitis B virus. Homozygotes for a polymorphism at codon 352 (genotype tt) were significantly underrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
267
4
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 385 publications
(288 citation statements)
references
References 14 publications
13
267
4
4
Order By: Relevance
“…Furthermore, it harboured the SNPs ApaI in intron 8 and TaqI in exon 9 (Fig. 1B), both previously implicated in TB susceptibility [10][11][12][13][14]. TaqI and rs4987032 (immediately upstream of TaqI in exon 9) could directly affect methylation due to their respective location in CpGs 5 and 6 of CGI 1060.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Furthermore, it harboured the SNPs ApaI in intron 8 and TaqI in exon 9 (Fig. 1B), both previously implicated in TB susceptibility [10][11][12][13][14]. TaqI and rs4987032 (immediately upstream of TaqI in exon 9) could directly affect methylation due to their respective location in CpGs 5 and 6 of CGI 1060.…”
Section: Discussionmentioning
confidence: 91%
“…From a genetic perspective, it is still uncertain whether TaqI or a linked marker is associated with TB. For example, the tt genotype, which is often associated with lower bone mineral density, was found less frequently in patients with pulmonary TB in The Gambia [10] but was not confirmed in a subsequent West African study that supported VDR haplotype association [11], similar to a South African study [12]. A study in India showed the tt genotype to be associated with TB [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic analysis of a complex trait such as susceptibility to tuberculosis is extremely difficult in humans due to variable pathogenicity determinants of the bacterium, unequal exposure, incomplete penetrance, phenocopies, locus heterogeneity, and polygenic effects. 4 Case-control studies in endemic areas of tuberculosis using candidate genes have revealed association of susceptibility to disease with alleles of genes encoding the macrophage natural resistance protein NRAMP1, 9 the vitamin D receptor, 10 and HLA-DQ 11 in specific populations. However, the overall effect of these genes is acknowledged to be small, and other genes are certain to play a role in susceptibility to human tuberculosis.…”
Section: Introductionmentioning
confidence: 99%